2011
DOI: 10.5301/ijao.2011.8458
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Perfusion Preservation for Expanded-Criteria Donors Kidneys: Impact on Delayed Graft Function Rate

Abstract: Pulsatile perfusion preservation significantly reduced DGF rate in ECD kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…Based on the search strategies and selection criteria, we included seven studies comparing HMP to CS in this review [5], [17]–[22], involving 2374 and 8716 kidney grafts with HMP and CS preservation respectively, all from ECD donors. Of these seven studies, two were randomized controlled trials(RCTs), one was a prospective study, and four were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the search strategies and selection criteria, we included seven studies comparing HMP to CS in this review [5], [17]–[22], involving 2374 and 8716 kidney grafts with HMP and CS preservation respectively, all from ECD donors. Of these seven studies, two were randomized controlled trials(RCTs), one was a prospective study, and four were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported the incidence of PNF after transplantation[5], [17], [18], [20], [21]. One study defined PNF as a permanent lack of function of the allograft from the time of transplantation[5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the effects of 30–90 minutes of warm renal ischemia per se produce measured reperfusion injury to the kidney at transplantation, the addition of inevitable periods of hypothermia from traditional organ preservation, no matter how brief, produces potentiating injury that exceeds the sum of both factors combined [4, 5]. This typically results in very high incidence of delayed graft function (DGF) following transplantation [6]. …”
Section: Introductionmentioning
confidence: 99%